The Fate of Theology after the Speculative Turn - Polidori, Troy (ThéoRèmes, 2014)
It will be our contention that the religious turn in continental philosophy has little to offer the domain of theology, despite the resurgence of interest in the latter on account of the historical trajectory of the former, and that, consequently, speculative theologians should welcome Meillassoux’s ‘critique of Critique’. We will come to see that Meillassoux’s work has opened up a space for theological discourse, albeit one limited on polarized ends: on the one hand, Meillassoux's rejection of dogmatic pre-critical metaphysics, and on the other, the judgment that contemporary continental philosophy of religion is an historical error based on the faulty reasoning of post-Kantian epistemological finitism. The former pole guards against the vampiric return of classical metaphysical theology, and the latter warns of the dangers associated with various contextual theologies, stemming as they do from the “religionizing of reason”. Our proposal will be that a specific form of theology can find its way through this narrow passage, and that a thorough rapprochement with Meillassoux’s critique of religious and theological thought in After Finitude can be had without completely abandoning theological discourse.